2013
DOI: 10.15343/0104-7809.2013373329335
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da aquisição de gêneros alimentícios provenientes da agricultura familiar para a alimentação escolar

Abstract: The Efficient Manager of School Meals Prize organized by the non-governmental organization Ação Fome Zero, identifies and rewards municipalities with good municipal public administration of the National School Feeding Program (PNAE). The purpose of this study was to evaluate the acquisition of food items from family farming by municipalities that registered and were selected to receive the prize. The study used data from the 8 th edition of the 2011 Prize regarding the report given by municipalities about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
20

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 2 publications
(2 reference statements)
3
15
0
20
Order By: Relevance
“…The same study by Toyoyoshi et al 9 , the only study in the literature that assessed the profile of foods acquired from family farms, found that the food groups most acquired by 83.0% of the 19 winning cities were fruits/pulps and vegetables, a result similar to that of the present study despite the use of different methods. One can infer that family farm products can encourage students to consume fruits and vegetables, a consumption that is still low as pointed out by Levy et al 20 , who analyzed data from the Pesquisa Nacional de Saúde do Escolar (PeNSE, National Student Health Survey) to determine how often students consumed eight foods, food groups, or preparations, and found that 21.0% of the students did not consume fruits, and 26.8% did not consume vegetables at all.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The same study by Toyoyoshi et al 9 , the only study in the literature that assessed the profile of foods acquired from family farms, found that the food groups most acquired by 83.0% of the 19 winning cities were fruits/pulps and vegetables, a result similar to that of the present study despite the use of different methods. One can infer that family farm products can encourage students to consume fruits and vegetables, a consumption that is still low as pointed out by Levy et al 20 , who analyzed data from the Pesquisa Nacional de Saúde do Escolar (PeNSE, National Student Health Survey) to determine how often students consumed eight foods, food groups, or preparations, and found that 21.0% of the students did not consume fruits, and 26.8% did not consume vegetables at all.…”
Section: Discussionsupporting
confidence: 89%
“…Toyoyoshi et al 9 assessed cities that participated in 2011's Prêmio Gestor Eficiente (Efficient Manager Prize) conducted by the nongovernmental organization Ação Fome Zero (Zero Hunger Program) and found that 19 of the 22 winning cities acquired foods from family farms. Of these, three acquired regional products: pequi (Caryocar brasiliense) (Mato Grosso), taioba (Xanthosoma sagittifolium) (Minas Gerais), caruru (Amaranthus species) and jambo (Syzygium jambos) (Pará), and two other cities from the states of Paraíba (PB) and Ceará (CE) acquired organic foods, corroborating the results observed by the present study in which public procurements within rural family farming rarely request regional and organic foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study nationwide was identified that eight of the 18 cities analyzed also acquired over 30% of the resource (TOYOYOSHI et al, 2013). Considering only the Brazilian southeast region, the purchase over 30% was reported by 42.4% of cities (SARAIVA et al, 2013).…”
Section: Resultsmentioning
confidence: 89%
“…Fruit, legume and vegetables (FLV) represented 77.2% of total food purchases by FF (Table 1). In a study developed by TOYOYOSHI et al (2013), the fruit or pulp of fruits and vegetables were purchased by 83% of the cities to be the most available food.…”
Section: Resultsmentioning
confidence: 99%